LEARNING OF REACTION RATES WITH NESTED CURRICULAR ARRANGEMENT WHICH IS COMBINED WITH CONNECTED CURRICULAR ARRANGEMENT TO IMPROVE CRITICAL THINKING SKILLS OF THE STUDENTS - Khoirotus Sa'adah; Suyono Suyono (JCER (Journal of Chemistry Education Research), 2020)
Abstract. This study aims to evaluate a learning of reaction rates with nested curricular arrangement which is combined with connected curricular arrangement to improve critical thinking skills of the students. The evaluation of this study is based on the result of data collecting toward the implementation of learning, students activities, learning outcomes, critical thinking skills, and students responses. This study is conducted using scientific inquiry. The research design used in this study is one group pretest-posttest design including pre-experimental research. The subjects of this study are 36 X graders of MIPA 8 at SMAN 1 Manyar Gresik. The result of this study shows that the implementation of a learning of reaction rates with nested curricular arrangement which is combined with connected curricular arrangement to improve critical thinking skills of the students is in very high value category with percentage of agreement around â‰¥75% and value of the relevant students activity is greater than the percentage of the irrelevant students activity so that it has a better category. The students learning outcomes and critical thinking skills have significantly improved after conducting a learning about reaction rates with nested curricular arrangement which is combined with connected curricular arrangement which is analyzed using t-test. However, there are some students get post-test score under the expected standard value. This learning about reaction rates with nested curricular arrangement which is combined with connected curricular arrangement receives a positive responses from the students of 87, 22% by collecting data using a questionnaire response.Keywords: Critical Thinking Skills, Inquiry, Nested, Connected